Comparison of In-Person Counseling and Telephone Support on Delivery Self-Efficacy in Primiparous Women - Farnoush Khojasteh; Zahra Eshteharian Dokht; Hossein Ansari (Mashhad University of Medical Sciences, 2018)
Introduction: Enhancing the mothers' knowledge and proper education during pregnancy is of the important factors in preparing the mothers for the process of delivery. According to Bandura's social learning theory, self-efficacy refers to the individual's confidence in his ability to behave in a way leading to the desired outcome. This study was performed with aim to compare in-person counseling and phone support on delivery self-efficacy in primiparous women. Methods: This double-blind randomized clinical trial was conducted on 163 primiparous women aged 18-35 years old who referred to Zahedan health centers in 2017. Subjects were placed in three intervention and control groups. At 20-32 weeks of pregnancy, in-person counseling group received four sessions of 60 minutes counseling and phone support group received four sessions of 20 minutes phone counseling. Control group received routine cares. Data were collected using demographic questionnaire, delivery self-efficacy, and homework registration form. The pretest was completed at 20 weeks and posttest was completed at 34-36 weeks of pregnancy. Data was analyzed using SPSS software (version 19) and by non-parametric tests of Kruskal-Wallis and Wilcoxon. P<0.05 was considered statistically significant. Results: Before the intervention, no significant difference was found among the groups in terms of self-efficacy scores. After the intervention, the mean score of self-efficacy increased in in-person counseling group (P <0.0001) than phone support group (P <0.001), but it did not significantly increase in the control group (P=0.57). Conclusion: In-person counseling is more effective than phone support n enhancing the delivery self-efficacy.